Navigating the BANI Era in Nursing Education Programs: Aligning Competencies with AUN-QA Criteria for Future-Ready Nursing Professionals. - Dumrongpakapakorn, Phensiri; Punaglom, Nedruetai; Na Sakonnakhon, Nuttiya Prommasaka (Pacific Rim International Journal of Nursing Research)
The shift from a VUCA (Volatile, Uncertain, Complex, Ambiguous) world to the BANI (Brittle, Anxious, Nonlinear, Incomprehensible) era brings unique challenges to healthcare, demanding a re-evaluation of essential competencies for nursing professionals. This article identifies five core competencies critical for nursing personnel in the BANI era: adaptability, emotional resilience, technological and digital literacy, interdisciplinary collaboration, and ethical decision-making. A comprehensive learning program is proposed to develop these competencies in nursing students, emphasizing alignment with ASEAN University Network-Quality Assurance (AUN-QA) criteria, specifically Criteria 1-8, to ensure educational quality and relevance. Detailed learning modules are outlined, each structured to support competency development through evidence-based teaching methods, while Criteria 5 (Academic Staff), 6 (Student Support Services), and 7 (Facilities and Infrastructure) reinforce the program's foundational support. Assessment strategies are integrated to focus on outcome-based education, evaluating graduates' readiness to meet the demands of the modern healthcare environment. Additionally, the potential for adapting this competency-based program to other health science disciplines is discussed, underscoring its wider applicability across the healthcare sector.